CURRENT STATE OF THE PROBLEM OF FORMATION OF ECOLOGICAL CULTURE OF FUTURE TEACHERS BIOLOGY (Pedagogy of Higher and Secondary Education, 2007)
This article is devoted to the modern problems of ecological culture forming of future Biology school-teachers.